Development of a syrup based on blood and honey (Ciencia y Tecnología de Alimentos, 2025)
Iron deficiency anemia is the hematological condition of greater prevalence in pregnant women, can compromise pregnancy, childbirth or fetus. The objective of the study was to develop a syrup for the feeding of this population sector, based on blood and honey with adequate quality, compositional, sanitary and sensory characteristics. To the product obtained, the determinations were made moisture, protein, iron, pH, water activity, soluble solids, count of microorganisms at 30°C, count of total coliforms, thermo tolerant coliforms, yeasts and molds. For the sensory evaluation, the taste characteristics were considered, smell, texture, and the bloody aftertaste, which were evaluated by seven trained tasters using a linear scale of 10 cm in length of increasing intensity from left to right, limited at both ends from absence to very marked, and in the case of the overall sensory quality, with extremes of with extremes from bad to excellent. The supplement presented a moisture content of   7.0%, proteins 0.52%, water activity values of 0.84 and pH of 4.7. The iron content of the syrup is 15.4 mg / 100 g of product, guarantees in a tablespoon of the same 2.8 mg of iron, being 10% of the recommended daily intake for pregnant women. The microbiological indicators of the product, fulfilled established specifications endorsing its adequate sanitary hygienic quality. The supplement developed was characterized as a syrup of taste and smell typical to the additive of flavor used, sweetness and moderate viscosity, and without blood aftertaste.
Keywords: anemia, nutritional supplement, pregnant women